ASIAN experiences of regional and Inter regional cooperation : relevance for SAARC - Bangladesh Institute of International and Strategi (Dhaka : Bangladesh Institute of International and Strategi, 1988)
'Public Administration' develops a comprehensive understanding of the internal structure and functioning of government in all its complexity and its interaction with society and its citizens.
Includes bibliographical references and index.
Description based on print version record.
Keywords: International Cooperation